2015
DOI: 10.1134/s0010508215020094
|View full text |Cite
|
Sign up to set email alerts
|

Gas-disperse synthesis of metal oxide particles

Abstract: The main results of years of research of metal dust flames aimed at the development of the scientific basis for the method of gas-disperse synthesis of metal oxide nanopowders are discussed. Methods of burning metal dust in oxide-containing media, the key problems of gas-disperse synthesis, and possible ways to solve these problems are considered. The ways of controlling the disperse composition of vapor-phase and gas-phase combustion products of metal particles by variation of the macroparameters of the dust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
15
0
2
Order By: Relevance
“…Indium thin oxide coated glass plate was used as solid support. ZnO nanorods were deposited as powder by gaseous disperse method as explained in previous methods [12]. PANI was synthesized by oxidative-chemical deposition method [13].…”
Section: Zno Deposition and Formation Of Zno-pani Compositementioning
confidence: 99%
“…Indium thin oxide coated glass plate was used as solid support. ZnO nanorods were deposited as powder by gaseous disperse method as explained in previous methods [12]. PANI was synthesized by oxidative-chemical deposition method [13].…”
Section: Zno Deposition and Formation Of Zno-pani Compositementioning
confidence: 99%
“…For instance, nanosized silica particles in fluid flow (nanofluid flow) alter physics and mechanics of heat exchange processes compared with pure fluid flow [2]. One of the conventional techniques of gas-disperse synthesis of metal oxide particles is based on oxidation of metal vapors [3]. In [1] a comprehensive review of vapor-phase synthesis of ceramic oxide particles (in particular, SiO 2 nanoparticles), analysis of gas-phase and nucleation kinetics as well as modeling of physico-chemical phenomena accompanying particle formation and growth is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Specifi cities of condensation of the ionized products in the metal dust fl ame in relation to the controlled synthesis of metal oxide nanoparticles was investigated in [5][6][7]. In [6] it is shown that in the conditions of metal dust fl ames, which are the source of metal oxide nanoparticles, nucleation is "fast" [1] .…”
Section: Nucleation In the Ionized Dusty Fl Amesmentioning
confidence: 99%
“…The great interest are unusual mechanisms of mass and heat transfer induced by the electric interaction between electrically charged particles of fuel and gas ions [4]. The complex plasma of the fuel combustion products makes the strong infl uence on the processes of condensation in fl ame [5][6][7].…”
Section: Introductionmentioning
confidence: 99%